Waqf, Maqasid al-Sharia, and SDG-5: A Model for Women’s Empowerment - Aam Rusydiana; Raditya Sukmana; Nisful Laila; Sherrindra Avedta (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This study aims to provide an alternative waqf model as Islamic social finance in realizing Sustainable Development Goals (SDGs)-5, namely gender equality and correlate it with Maqashid al-Sharia. This study uses the Analytic Network Process (ANP). ANP is needed in the problem decomposition framework to structure complexity. There are 16 experts as the respondents. From the results of the ANP, it will also be known what the SDGs criteria, maqashid al-sharia components, and waqf models are priorities in realizing the 5th SDGs. The findings of this study reveal that among the other two, social pillars are the main criteria for the SDGs. In addition, the maqashid al-sharia framework's main objective is preserving religion (deen) as a means of enforcing religious responsibilities. Therefore, stakeholders need to consider this element. Then, according to this study, the best alternative waqf model is Waqf & Zakat, Infaq, Shadaqah (ZIS), which is very suitable for gender equality within the framework of women's empowerment in terms of education, entrepreneurship, and other life skills.